ARF2‐PIF5 interaction controls transcriptional reprogramming in the ABS3‐mediated plant senescence pathway. (9th August 2022) - Xue, Hui; Meng, Jingjing; Lei, Pei; Cao, Yongxin; An, Xue; Jia, Min; Li, Yan; Liu, Haofeng; Sheen, Jen; Liu, Xiayan; Yu, Fei
Abstract: One of the hallmarks of plant senescence is the global transcriptional reprogramming coordinated by a plethora of transcription factors (TFs). However, mechanisms underlying the interactions between different TFs in modulating senescence remain obscure. Previously, we discovered that plant ABS3 subfamily MATE transporter genes regulate senescence and senescence‐associated transcriptional changes. In a genetic screen for mutants suppressing the accelerated senescence phenotype of the gain‐of‐function mutant abs3‐1D, AUXIN RESPONSE FACTOR 2 (ARF2) and PHYTOCHROME‐INTERACTING FACTOR 5 (PIF5) were identified as key TFs responsible for transcriptional regulation in the ABS3‐mediated senescence pathway. ARF2 and PIF5 (as well as PIF4) interact directly and function interdependently to promote senescence, and they share common target genes such as key senescence promoting genes ORESARA 1 ( ORE1 ) and STAY‐GREEN 1 ( SGR1 ) in the ABS3‐mediated senescence pathway. In addition, we discovered reciprocal regulation between ABS3‐subfamily MATEs and the ARF2 and PIF5/4 TFs. Taken together, our findings reveal a regulatory paradigm in which the ARF2‐PIF5/4 functional module facilitates the transcriptional reprogramming in the ABS3‐mediated senescence pathway. Synopsis: The late endosome‐localized ABS3 subfamily of MATE transporters regulates senescence and senescence‐associated gene expression through mechanisms which are not well understood. Here, developmental transcription factors ARF2 and PIF5/4 are found to interact to control transcriptional regulation in the ABS3‐mediated senescence pathway. Mutations in ARF2 and PIF5 suppress precocious senescence caused by abs3‐1D, a gain‐of‐function mutant allele of ABS3 . ARF2 and PIF5/4 can regulate senescence both together and independently. ARF2 and PIF5 physically interact and share common target genes, such as the key senescence‐promoting genes ORE1 and SGR1 . ABS3‐subfamily MATEs and the ARF2‐PIF5/4 functional module regulate each other's activity to fine‐tune senescence. Abstract : Two distinct plant transcription factors known to mediate key developmental programs are shown to cooperate to control senescence.